Preoperative Assessment of Cervical Vestibular Evoked Myogenic Potentials (cVEMPs) Help in Predicting Hearing Preservation After Removal of Vestibular Schwannomas Through a Middle Fossa Craniotomy. Issue 10 (December 2018) - Hochet, Baptiste; Achard, Sophie; Lorenz, Mark Brandt; Baroncini, Marc; Berama, Amine; Gabanou, Frederic; Devambez, Marion; Lejeune, Jean-Paul; Vincent, Christophe; Bonne, Nicolas-Xavier
Abstract : Objective: To determine whether cervical vestibular evoked myogenic potentials (cVEMPs) are predictive of hearing preservation in patients undergoing vestibular schwannoma removal through middle fossa craniotomy approach. Study Design: Retrospective case study. Setting: Tertiary referral center. Patients: Eighteen patients who underwent a middle fossa craniotomy for vestibular schwannoma (stage I or II of Koos classification) with attempted hearing preservation from January 2008 to February 2016 were retrospectively reviewed. Intervention: Pre-surgical cVEMPs test, videonystagmography (caloric test), and magnetic resonance imaging (MRI) as well as a pre- and post-surgical audiometry test. Main Outcome Measures: cVEMPs parameters including amplitude asymmetry ratio (AR), P13, and N23 latencies and peak-to-peak amplitude between P13 and N23 waves were calculated. Hearing data were classified according to the AAO-HNS hearing classes. The nerve of origin of the tumor was specified during surgery and the largest tumor diameter was measure on MRI axial plane on T2-CISS weighed images. Results: Preoperative amplitude asymmetry ratio was lower (n = 15, Mann–Whitney U test, p < 0.001) in the group with postoperative hearing preservation (n = 11) compared with the group with postoperative hearing preservation failure (n = 4). The positive predictive value of an AR less than 24% to assess postoperative hearing preservation is 91.6%. Tumor size and localization were not correlated with cVEMPs, nor with caloric testing in this group of small-sized intracanalicular vestibular schwannomas. Conclusions: Our data suggest that cVEMPs may help predict hearing preservation outcome in vestibular schwannoma surgery via the middle fossa craniotomy approach.